Analysis Of The Dependency And Efficiency Ratios If Catur Rahayu Village From 2020 To 2022: Analysis Of The Dependency And Efficiency Ratios If Catur Rahayu Village From 2020 To 2022 - Ihsan, M. Ihwanul; Mansur, Fitrini; Safelia, Nela (Jurusan Akuntansi FEB Universitas Jambi, 2025)
Financial ratio analysis of the Village Revenue and Expenditure Budget (APBDes) is one of the parameters used to measure the financial management performance of a village. Financial performance analysis was conducted using dependency and efficiency ratio calculations to measure the financial performance of the Catur Rahayu Village Government for the 2020-2022 period. The type of research used is descriptive, using a qualitative and quantitative approach. The results of the study show that the dependency ratio with an average of >96.22% per year in the very high category indicates that Catur Rahayu Village is highly dependent on transfer funds from the local or provincial government. Meanwhile, the efficiency ratio of Catur Rahayu Village from 2020 to 2022 is classified as inefficient, with an average efficiency ratio of >96.86% per year. This indicates that the financial management of Catur Rahayu Village is not yet optimal in terms of exploring its potential to increase its own-source revenue and managing its expenditures efficiently.